2003
DOI: 10.1021/es0347282
|View full text |Cite
|
Sign up to set email alerts
|

Human-Cell Mutagens in Respirable Airborne Particles in the Northeastern United States. 1. Mutagenicity of Fractionated Samples

Abstract: Few studies have characterized the regional scale (300-500 km) variability of the mutagenicity of respirable airborne particles (PM2.5). We previously collected 24-h PM2.5 samples for 1 year from background, suburban, and urban sites in Massachusetts (MA) and rural and urban sites in upstate New York (NY) (n = 53-60 samples per site). Bimonthly composites of these samples were mutagenic to human cells. The present report describes our effort to identify chemical classes responsible for the mutagenicity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 40 publications
(69 reference statements)
1
46
0
3
Order By: Relevance
“…In addition to direct mutagenicity and carcinogenicity [4,5], in vivo assays have shown that quinones are highly redox active, cascading the formation of reactive oxygen species (ROS) within the cell [6]. The presence of ROS can cause severe oxidative stress within cells [7] and lead to the development of diseases and pathological conditions such as asthma, cardiovascular diseases, Alzheimer, diabetes, or cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct mutagenicity and carcinogenicity [4,5], in vivo assays have shown that quinones are highly redox active, cascading the formation of reactive oxygen species (ROS) within the cell [6]. The presence of ROS can cause severe oxidative stress within cells [7] and lead to the development of diseases and pathological conditions such as asthma, cardiovascular diseases, Alzheimer, diabetes, or cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their recognized or potential mutagenic activity (Arey et al, 1988;Durant et al, 1996;Ishii et al, 2000;Pedersen et al, 2004Pedersen et al, , 2005, the study of PAH derivatives according to the particle size distribution is of prime interest. However, to date, only 8 authors reported results on the size distribution of NPAHs (Ladji et al, 2009;Hayakawa et al, 1995b;Albinet et al, 2008a;Cecinato et al, 1999;Di Filippo et al, 2010;Hayakawa et al, 1995a;Jinhui and Lee, 2000;Kawanaka et al, 2004Kawanaka et al, , 2008Teixeira et al, 2011), and only 4 papers focused on the particle size distribution of OPAHs (Albinet et al, 2008a;Allen, 1997;Allen et al, 1997;Ladji et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample literature showing that PM is toxic to humans (IARC Monographs on the Evaluation of Carcinogenic Risks to Humans 1989; Peng et al 2005). More recently, a direct link between the PAH content of atmospheric PM and adverse health effects has been established (Pedersen et al 2004;Xia et al 2004). …”
Section: Introductionmentioning
confidence: 99%